Deception point - Brown, Dan (Pocket Books, 2001)
When a new NASA satellite detects evidence of an astonishingly rare object buried deep in the Arctic ice, the floundering space agency proclaims a much-needed victory...a victory that has profound implications for U.S. space policy and the impending presidential election.